2022
DOI: 10.3390/agronomy12071689
|View full text |Cite
|
Sign up to set email alerts
|

Copper Distribution and Binding Affinity of Size-Fractioned Humic Substances Taken from Paddy Soil and Correlation with Optical Characteristics

Abstract: Soil organic matter (SOM) is heterogeneous and a complex mixture, whose concentration, chemical composition, and structure are strongly associated with the binding behavior of heavy metals (HMs) in soil. The HM-SOM binding affinity affects the HM biotoxicity and bioavailability in the environment. This study investigated Cu’s distribution and binding affinity on five size-fractioned alkaline-extracted soil organic matters (AEOMs) taken from paddy fields. The fractioned AEOMs were M-A (100 kDa −0.45 μm), M-B (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The CuBA AEOM ratios at site-1 and site-2 were 111.2 ± 10.2 and 108.7 ± 8.7 µmol g-C −1 , respectively, which were higher than the CuBA ratios of the soil solution (ranging from 3.7 to 20.2 µmol g-C −1 ), water, and CaCl 2 extracted soil organic matter (ranging from BLD to 34.0 µmol g-C −1 ), and NaOH extracted soil and sediment organic matter (ranging from 13.2 to 56.2 µmol g-C −1 ) [21,22,37]. The CuBA DOM ratios showed a wide variation, as observed during in-field measurements.…”
Section: Cuba Ratios Of Dom and Aeommentioning
confidence: 85%
See 3 more Smart Citations
“…The CuBA AEOM ratios at site-1 and site-2 were 111.2 ± 10.2 and 108.7 ± 8.7 µmol g-C −1 , respectively, which were higher than the CuBA ratios of the soil solution (ranging from 3.7 to 20.2 µmol g-C −1 ), water, and CaCl 2 extracted soil organic matter (ranging from BLD to 34.0 µmol g-C −1 ), and NaOH extracted soil and sediment organic matter (ranging from 13.2 to 56.2 µmol g-C −1 ) [21,22,37]. The CuBA DOM ratios showed a wide variation, as observed during in-field measurements.…”
Section: Cuba Ratios Of Dom and Aeommentioning
confidence: 85%
“…This correlation suggested the complex sources of the DOM in the present study. In a soil NaOH extracted study, the CuBA AEOM ratios of size-fractioned AEOM exhibited a significantly negative correlation with indicators FI and BIX [37]. Hence, high CuBA ratios followed high aromaticity, terrestrial and allochthonous sources in soil and sediment solutions.…”
Section: Correlation Between Cuba Ratios With Optical Indicesmentioning
confidence: 88%
See 2 more Smart Citations
“…Copper ions' distribution and affinity in five size-fractioned alkaline-extracted soil organic matters from paddy fields containing humic substances were investigated by W.-H. Huang, T.-C. Lin, C.-M. Huang, T.-C. Chen, and Y.-L. Yeh in their article on the "Copper Distribution and Binding Affinity of Size-Fractioned Humic Substances Taken from Paddy Soil and Correlation with Optical Characteristics" [5]. The results showed that Cu preferably associated with fractions of high aromaticity.…”
mentioning
confidence: 99%